Maritime Piracy and its Implications on Security in the Gulf of Guinea - Ken Ahorsu; David Suaka Yaro; Derrick Attachie (Eastern African Journal of Humanities and Social Sciences)
The purpose of the study is to determine how piracy poses security challenges in the Gulf of Guinea. Document analysis method was used to analyse literature related to piracy in the Gulf of Guinea. The theory employed is the securitization of pioneered by Barry Buzan, Ole Waever, and Jaap de Wilde (1990).  Also, a retrospective cohort design is used for the study. The findings of the study revealed that the domestication of the Code of Conduct and other legal frameworks will ensure that national laws align with international maritime laws and provide a legal basis for addressing maritime crimes, including piracy. The proffered recommendation is that the government should actively engage pirates and other stakeholders in dialogue and contribute significant resources to ameliorate the environmental and economic damage caused by the oil industry.